Hubungan Panjang Aksial Bola Mata Dengan Derajat Miopia di Rumah Sakit Mata Makassar Tahun 2023-2024 - Achmad Giffary; Andi Sengngeng Relle; Nursapriani (RS Mata Makassar, 2026)
Background: Myopia is a refractive error where light falls in front of the retina, one of which is caused by an increase in axial length of the eyeball. Every 1 mm increase in axial length can increase refraction by 2.00 to 3.00 diopters. Objective: This study aims to determine the relationship between axial length of the eyeball and the degree of myopia based on age and gender in patients at Makassar Eye Hospital in 2023-2024. Methods: This study used an analytic observational design with a prospective cohort approach. The sample consisted of 203 patients (406 eyes) with myopia who met the inclusion and exclusion criteria, selected by purposive sampling. Secondary data was obtained from medical records of Biometric A- scan examination results. Data analysis was performed univariately and bivariately using T- sample test. Results: There was a significant relationship between axial length of the eyeball and age, gender, and degree of myopia (p<0.05). The mean axial length in mild myopia was 24.12 mm, moderate myopia 25.02 mm, and high myopia 27.06 mm. Males had a greater axial length (25.29 mm) compared to females (24.81 mm). Conclusion: Axial length of the eyeball plays an important role in determining the degree of myopia. Axial length measurement can be an important indicator for early detection and management of myopia, especially in high-risk groups.